QUALITY ASSESSMENT OF YOGHURT PRODUCED AT LARGE (I NDUSTRIAL) AND SMALL SCALE - Ahmad; I .; M. Gulzar; F. Shahzad; M. Yaqub; T. Zhoor (Journal of Animal and Plant Sciences, 2013)
The quality of fermented dairy products is a delicate subject. In addition to processing conditions, it largely depends on pre and post process handling. The present study is concerned with the physicochemical and microbiological quality of commercially available yogurt in Faisalabad, Pakistan. For this purpose, two branded (produced at large scale) and three unbranded (produced at small scale) yoghurt samples were collected from the city and were analyzed in triplicate. The data was analyzed by complete randomized design (1-factor factorial) and comparison of means was done by Duncan’s multiple range test. The coliform count in branded samples was nil or ignorable. However, unbranded samples contained a higher count of coliforms. The branded samples were monocultured (S. thermophilus), which does not fulfill the quality criteria as L. bulgaricus is also needed for good quality yoghurt. In contrast, in unbranded samples, both the bacteria were present but their growth was uncontrolled. The fat, lactose and total solid contents were low in unbranded yoghurt samples than in branded samples showing lack of standardization. However, acidity and syneresis value of branded samples were low as compared to unbranded samples.
Keywords: Yoghurt quality; yoghurt culture; Physicochemical quality; Microbiological quality; Commercial market